Stitched Together : Stories of a Kentucky Life - Thompson, Bob, 1950 August 8- (Book collections on Project MUSE., 2019)
"Stories represent snapshots in time-each unique to the lives who lived them; each imparting wisdom in different ways to those who take the time to stay and listen. As a child, Bob Thompson had nothing but time, passing his days on the front porch of his Granny's country store in Western Kentucky. His closest friends were his grandmother and the regulars at Ogden Landing Road grocery who would readily stop to swap stories and spin yarns. Those experiences led Thompson to discover his own passion for storytelling, and he has been sharing his tales with audiences since the early 1980s, constantly honing his unique style and personal delivery. In Stitched Together, Bob Thompson returns to his roots in a new exploration of both his early life in Kentucky as well as the adventures that have taken him around the world. However, as in his first book, it is the characters of his early life that shine most brightly. In the collection's first story, "Granny," Thompson explores the moments when he first began forming his stories. In the story, Granny is, in many ways, the grandmother we all know-a sweet, gentle, woman who is concerned for those around her, those close to her, but she also prepares to assist those she will never meet or see. It is here where both writer and audience discover new lessons, and learn the significance of quiet moments and the blank spaces that fill so much of our daily lives as Granny recounts the life and stories of family members passed. With a lifetime of experiences, Thompson spotlights the rich historical past of Western Kentucky, its legends, and its people. Sometimes humorous, sometimes dark, these accounts will be of interest to a cross-generational audience. As with his celebrated first book, Stitched Together is equal parts Huckleberry Finn and The Twilight Zone, with just a taste of The Electric Kool-Aid Acid Test"--